Lesson study implementation: How is the students’ language learning motivation? - Asep Hardiyanto (UAD TEFL International Conference)
The current article attempts to elaborate on the students’ language learning motivation within the application of lesson study for the learning community at STKIP Muhammadiyah Kotabumi. This article is a descriptive-quantitative study involving 60 students of the English Education Study Program as the sample. A questionnaire to identify the language learning motivation is administered as the instrument of the research. The questionnaire is validated by experts and the reliability is tested using Cronbach Alpha formula. The data are analyzed descriptively. The findings show that the students’ language learning motivation within a lesson study framework tends to be instrumental orientation. Therefore, lesson study for a learning community is effective to be implemented at STKIP Muhammadiyah Kotabumi, especially for the students of the English Education Study Program.